United States agricultural policy: Its evolution and impact - Glauber, Joseph W.; Effland, Anne (International Food Policy Research Institute, 2016)
This paper examines the development of US agricultural policy and considers how it has affected US consumers and producers, as well as how US programs affect foreign producers and consumers within the context of the United States’ obligations under the World Trade Organization. Throughout its history, the United States has supported the farm sector through a myriad of policies affecting prices, production, and farm incomes. Although many of the policies put in place during the New Deal legislation in the 1930s were seen as temporary at the time, most have persisted in one form or another to the present day. And while many would argue that the form and function of today’s agricultural programs are less distortionary than before, the level of support provided to the sector is several billion dollars annually.